Effects of vertical shear on intensification of tropical cyclones of different initial sizes - Bi, Mingyu; Wang, Ruifang; Li, Tim; Ge, Xuyang (Frontiers in Earth Science, 2023)
The idealized experiments are conducted to examine the impacts of moderate vertical wind shear (VWS, i.e, the magnitude of 12 m s-1) on the intensification of tropical cyclones with different initial sizes. The results show that the intensity of all the simulated TCs decrease at the first 12-h integration after imposing the shear. Larger TC resumes to intensify earlier, whereas the smaller one re-intensifies more laggingly or even fails to intensify. The differences in the intensification rate is likely ascribed to the tilting magnitude. Under the VWS, the upper-level TC center exhibits a horizontal displacement relative to the low-level circulation. In general, this displacement is smaller in larger TC, indicating that larger TCs is less susceptible to VWS. Thermodynamically, the intrusion of mid-level low moist entropy also plays a role in suppressing upshear convection. This negative impact is pronounced in smaller TCs. By using PV-ω equation, the resilience of TC to VWS is compared. The second circulation forced by both dry dynamic and diabatic heating acts to restore the system be vertically upright. For larger TC, more extensive convection is prolific on downshear side, and its corresponding forced second circulation offset larger part low- to midlevel environmental shear which makes larger TC more resilient to VWS. Namely, larger TC produces stronger low to middle counter shear circulation, helping the vertical realignment. In contrast, for smaller TC, the updrafts forced by dry dynamic and diabatic heating are deeper but narrower at the initial time, which cannot efficiently reduce the mid-level VWS, resulting in the larger tilting of TC, thus making the smaller TC more vulnerable to VWS.